Incidences, trends and long term outcomes of retinoblastoma in three cancer registries, Thailand - Piyathida Wongmas (2018)
Background: Retinoblastoma (RB) is rare, albeit the most common primary intraocular malignancy among children. To elucidate the true incidence, trend and survival, we studied incidences and trends of retinoblastoma in a large population with long-term follow-up using data from 3 population-based cancer registries. Objective: To describe the incidence, trends and survival of RB between 1990 and 2009 in Khon Kaen, Songkhla and Chiang Mai, Thailand. Materials and Methods: We sourced the data from the cancer registries in Khon Kaen, Songkhla and Chiang Mai on children with retinoblastoma, diagnosed between 1990 and 2009. Retinoblastoma was defined as per the International Classification of Disease for Oncology version 3 using the code 9510/3. Incidence was analyzed using the standard method with the criteria of the International Association of Cancer Registries. The Kaplan-Meier method was applied to calculate cumulative survival. Trends were calculated using the log rank test. Results: We identified 75 cases of children between 0 and 15 years of age diagnosed with RB (Khon Kaen 31, Chiang Mai 20, Songkhla 24). Males and females were equally affected. The most common age group was 0-4 years. The morphological verification of the disease was 90.7%. The respective ASR in Khon Kaen, Chiang Mai and Songkhla was 4.4, 4.0 and 4.6 per million; for which the overall ASR for all 3 areas was 4.3 per million. The respective trend in incidence was 4, 2.8, 5.8 and 5.4 during 1990-4, 1995-9, 2000-4 and 2005-9. Overall, incidence trended gradually upward by 2% annually. The respective survival rate in Khon Kaen, Chiang Mai and Songkhla was 50, 40 and 75% (differences not significantly different at p=0.14) and the overall survival for all centers was 60%. Conclusions: Over the last two decades, the incidence and overall survival of retinoblastoma has increased. The ASRs and survival in Thailand were less than those in resource-rich countries.